TRANSLATING, TRANSLATION, AND HERMENEUTICS - Yamin, Moh. (Vidya Karya Jurnal Kependidikan, 2014)
Translating the text needs the capacity and the capability from the person who will be involved in that field. Translating does not only deals with the changing of words, phrases, sentence, and the like from the source language into target language. The activity of translating needs hermeneutics in order to get interpreting the text to be close to target language objectives. Text is not inanimate thing, but animate one that lives in its nature. Text is on the center of its readers. While being in the center of its readers, the text is doing the dialogue of meaning in inter and intra perspective.Â